Harmonie, la critique d’un « totalitarisme mou » par un roman japonais - Thomas Michaud (ReS Futurae)
The novel Harmony, by the Japanese author Project Itoh, addresses the theme of political resistance to a medical utopia realized. In the relatively near future, and after a terribly murderous nuclear war, the authorities have entrusted the organization of society to the medical community. Individuals are equipped with a technology that follows their health and prevents them from getting sick. Most diseases have been eradicated by this innovation, which also aims to purge Humanity of its destructive and bellicose tendencies. Young girls oppose this system according to a suicidal and terrorist rhetoric urging them to fight against a liberticidal "medicracy". This novel makes it possible to address the limits of innovations in the medical field. If the networking of medical data is supposed to improve the knowledge of diseases, it can also cause situations contrary to individual freedoms. The criticism of medicracy recalls the philosophy of Michel Foucault and his concept of biopolitics. The representations of this future without disease are part of the continuity of transhumanist and technopolitical discourses that announce for several decades the advent of what Lucien Sfez calls "the utopia of perfect health". The Japanese company is one of the most innovative in the world, as evidenced by the political will and the number of patents filed each year. It also regularly produces science fiction stories interviewing innovators about the ethics and morals of their discoveries and new products.